RECENT RESULTS TO BETA LYRAE'S NATURE ON THE BASE OF OBSERVATIONS WITH CCD-DETECTOR - Skulskyj, M. Yu. (Одеські астрономічні публікації, 2017)
The main results of the investigation of composed spectrum of massive interacting binary β Lyrae are reported. They are based on the study of dynamical and energetical parameters of the emission - absorbtion lines Si II 6347, 6371, Hα, He I 6678, 7065. The high resolution and S/N ratio red spectrogramms of β Lyrae system in general are obtained in 1990-1992 with CCD camera, incorporated into 2.6 m telescope of Crimea Astrophysical observatory.